The importance of early detection of Alzheimer's to improve the patient's quality of life - Nabosne, Isabella; Cruz, Rafaela Compri da; Borges, Beatriz Essenfelder (Seven Editora, 2024)
Alzheimer's disease is a progressive neurodegenerative disorder marked by behavioral and cognitive impairment that eventually interferes with daily functional activities. The disorder has no cure, and its rate of progression is variable. In this context, the early diagnosis of the disease is a valuable element so that the individual and their caregivers have time to make choices and plan, to allow access to treatments that can help manage the symptoms. Thus, the objective of this study is to present the importance of early diagnosis of Alzheimer's disease for a better quality of life for the patient. And for this, an integrative literature review was carried out, with inclusion criteria that included the original, free articles, available in full, in Portuguese, published in the last 5 years, which had a direct connotation with the theme and met the objective and perspectives of the study. Abstracts, duplicate copies, case studies, and those that did not meet the objective of the article were excluded. Alzheimer's disease represents an immense burden for people with the condition, for their families and caregivers, but also for the healthcare system and society at large, early diagnosis allows everyone involved to have time to adapt, while the patient can still actively participate contributing to the quality of life. We conclude that early detection, even though there is no cure, can be minimized with multidisciplinary follow-up and medication, contributing to well-being and quality of life, encouraging all those involved not to give up on the journey. DOI:https://doi.org/10.56238/sevened2024.001-004